Nós, professores: reflexões e memórias do trabalho com o ensino e aprendizagem de línguas (SciELO - Editus - Editora da UESC, 2020)
The eight texts gathered in the book bring the voice of teachers who daily experience the dilemmas and pleasures of the profession, presenting texts that are sometimes memoirs that engender reflections on pedagogical praxis, sometimes essays discussing concepts that support the didactic choices.